Assessment of the Diagnostic Accuracy of Eotaxin-2 as a Marker for Preterm Prelabour Rupture of Membranes - Ali, Miami Abdul Hassan; Ali, Naz Mazin (Scripta Medica, 2024)
Background/Aim: Preterm pre-labour rupture of the membranes could be caused by the change in local cytokines concentration due to inflammatory or infectious conditions. Cytokines, such as chemokine generated by immune cells that have been activated are the most extensive category of biochemical factors implicated in the development of preterm pre-labour rupture of the membranes (PPROM). Among this chemokine, eotaxin serves as a specific protein that attracts eosinophils. Aim of this study was to assess the diagnostic accuracy of eotaxin-2 as a marker for the diagnosis of PPROM. Methods: A case-control study was conducted in the Department of Obstetrics and Gynaecology at Bagdad Teaching Hospital, Iraq during a period of 10 months. The study sample included 90 pregnant women and was divided into three groups, the first group: 30 women with PPROM, the second group: 30 women with preterm labour and intact foetal membranes and the third group: 30 women at term pregnancy. For all women in the study blood samples were taken for measurement of eotaxin-2 at the same gestational age. Results: The eotaxin-2 level was found to be lower in cases of PPROM than in preterm labour and term cases. The sensitivity of eotaxin-2 was 83.3 %, specificity 70 % and negative predictive value 89.4 %. Conclusion: Eotaxin-2 might be considered as a marker for diagnosis of PPROM.